CHANGES IN PUBLIC INFORMATION CONSUMPTION PATTERNS IN THE DIGITAL ERA: A LITERATURE STUDY ON DIGITAL JOURNALISM - Indah Sulistiani; Caroline Caroline; Syarifuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Changes in the pattern of public information consumption in the digital era have brought about major transformations in the field of journalism. With easier access to information through various digital platforms and social media, people increasingly rely on mobile devices to get news quickly and instantly. This requires traditional media to adapt to new business models that are more oriented to audience needs and utilize the potential of data analysis to optimize content distribution. Digital journalism has emerged in response to these changes, offering a more interactive and engaging way of presenting news through the use of multimedia. However, there is a major challenge in maintaining the integrity and credibility of the news amid the rapid flow of information that is sometimes unverified. In facing this challenge, it remains important for journalists and media institutions to uphold the principles of ethics and professionalism in news reporting. Thus, the digital era provides opportunities as well as challenges for the world of journalism, requiring various parties to continue to innovate and prioritize the quality and accuracy of information presented to the public. Digital literacy and continuous training are crucial so that journalists and the public can adapt to the changes that occur, and still have access to credible and trustworthy information.